Heteroptera (Hemiptera) of the Southern Steppe agrocenosis on the example of the experimental fields of Odesa SAES ICSA NAAS - Uzhevska, S. P.; Drogvalenko, O. M.; Burykina, S. I.; Serhieiev, L. A. (The Kharkiv Entomological Society Gazette, 2026)
Heteroptera monitoring was conducted in 2022–2025 in the grain fields of the Odesa State Agricultural Experimental Station of the Institute of Climate-Smart Agriculture of the National Academy of Agrarian Sciences of Ukraine. There were registered 46 species of bugs from 13 families. Miridae (13) and Pentatomidae (7) dominated by the number of species. Phytophagous species prevailed by the type of feeding (87%), predators accounted for 9% and phytozoophagous species for 4%. In the fields of winter wheat, 43 species from 13 families were registered, spring barley — 17 species from 9 families, and winter-sown peas — 10 species from 8 families. It was found that the total number of true bugs in 2022–2023 was insignificant; the maximal number was recorded in 2024. Typical pests of grain crops (Eurygaster integriceps, Lygus rugulipennis) reached the threshold of harmfulness in 2024 and 2025. 2 figs, 2 tabs, 26 refs
Keywords: Hemiptera; pests; harmfulness; grain crops and legumes; Southern Steppe